(untitled) (SS Multidisciplinary Research Journal, 2024)
The primary objective of this study is to investigate the impact of Non-Performing Loans (NPLs) on Indonesian commercial banks, using data from the period 2016-2020. The data were gathered from the annual reports of Indonesian commercial banks. Purposive sampling techniques were employed to analyze the data. In this study, NPL is the dependent variable, and GDP, Inflation, Exchange rate, Bank Size, ROA, CAR, and IRL are the independent variables. The results indicate that Bank Size and Interest rates have a positive and significant effect on NPL in Indonesian commercial banks, while GDP, Inflation, Exchange rate, ROA, and CAR do not have a significant impact on NPL. These findings suggest that bank size and interest rates have a significant influence on NPL, and therefore, Indonesian commercial banks should take this into account seriously.